Microstructural, mechanical and electrical characterization of directionally solidified Al-Si-Mg eutectic alloy - Kaygisiz, Yusuf; Marasli, Necmettin (ELSEVIER SCIENCE SA, 2015)
Al-12.95 wt.% Si-4.96 wt.% Mg alloy was directionally solidified upward at a constant temperature gradient (G = 9.39 K/mm) with different growth rates (V= 8.64-165.20 mu m/s) by using a Bridgman type directional solidification furnace. The ternary eutectic alloy consists of irregular Si plates and Mg2Si Chinese's script within an aluminum matrix. The dependencies of lamellar spacings (lambda(si) and lambda(Mg2si)), microhardness, tensile strength and electrical resistivity on growth rates were obtained as HV = 119.9 (V)(0.07), sigma(t) = 222.84 (V)(0.20) and ana rho = 32.31 x 10(-8) (V)(0.13), respectively for Al-Si-Mg eutectic alloy. The bulk growth rates were determined lambda(2)(Si) = 847.69 and lambda V-2(Mg2Si) = 597.5 mu m(3)/s by using the measured values of lambda(Si), lambda(Mg2Si) and V. A comparison of present results was also made with the previous similar experimental results. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Directional solidification; Aluminum alloy; Microstructure; Electrical properties; Tensile test; Hardness test; GROWTH-RATE; CU-AG; TEMPERATURE-GRADIENT; PARAMETERS; MICROHARDNESS; HARDNESS; TRANSFORMATION; LAMELLAR; SPACINGS; PATH; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering